A CDRX-based material model for hot deformation of aluminium alloys. (November 2020) - Li, Yibo; Gu, Bin; Jiang, Shuai; Liu, Yaoqiong; Shi, Zhusheng; Lin, Jianguo
Abstract: During hot deformation, continuous dynamic recrystallisation (CDRX) is believed to occur, and even dominates microstructural evolution in many metallic materials with high stacking fault energy, such as aluminium alloys. A unique material model for hot deformation of aluminium alloys is proposed in this paper, based on consideration of two processes: (i) increase of dislocation density, induced by plastic deformation, leading to generation, rotation and migration of low angle grain boundaries (LABs) and their transformation into high angle grain boundaries (HABs); (ii) migration of HABs leading to annihilation of both LABs and HABs. At large strain, the above counteracting processes, guided by different mechanisms, lead to saturation of HABs fraction. The model is applied to hot deformation of AA5052 and AA7050 alloys under various temperatures and strain rates, and calculated flow stress, HABs fraction and grain size evolution for both alloys agree well with the corresponding experimental data. The capability of predicting saturation of HABs fraction and average subgrain misorientation angle of both alloys under large strains demonstrate the potential applicability of the model to a wide range of hot forming process conditions. Graphical abstract: Image 1 Highlights: A CDRX-based physical model for hot deformation of aluminium alloys is proposed and applied to AA5052 and AA7050. Contribution of dislocation density, subgrain rotation and grain boundary migration to microstructural evolution is modelled. Modelled flow stress agrees well with experimental data under various temperatures and strain rates. The model is suitable for hot forming process of aluminium alloys over a wide range of conditions.